Water chemistry data från Lake Erken, 1989-2015 - Yang, Yang (Uppsala University, 2018)
Water chemistry data from Erken from 1989 till 2015.

The dataset also include data for the publication:
Yang, Y., Pettersson, K. & Padisák, J. Hydrobiologia (2016) 'Repetitive baselines of phytoplankton succession in an unstably stratified temperate lake (Lake Erken, Sweden): a long-term analysis' 764: 211. https://doi.org/10.1007/s10750-015-2314-1

The Erken laboratory is located by the shore of lake Erken, 70 km northeast of Stockholm. A substantial lake measurement program has been running for the last 30 years, which includes manual sampling along with high frequency automatic measurements.

Columns:
Date, Year, Month, Week, Depth Stratification, Layer, Sec., pH, Alk, Cond, Col, Tur, SPM, SPOM, COD, Chl a, MRP/PO4-P, PP, dissP, SUP, Tot-P, NH4, NO2, NO3, NO2+NO3, PN dissN, Tot-N, Si

The data is free to use, but please inform us, so that we can keep track about the projects that make use of our data.

Vattenkemidata från Erken 1989 till 2015, insamlade av Erkens monitoringprogram.

Datasetet innehåller också data för artikeln:
Yang, Y., Pettersson, K. & Padisák, J. Hydrobiologia (2016) 'Repetitive baselines of phytoplankton succession in an unstably stratified temperate lake (Lake Erken, Sweden): a long-term analysis' 764: 211. https://doi.org/10.1007/s10750-015-2314-1

Erkenlaboratoriet är belägen vid stranden av sjön Erken, 70 km nordost om Stockholm. Stationen bedriver sedan ungefär 30 år tillbaka ett omfattande miljöövervakningsprogram av sjön Erken, som inkluderar manuella mätningar och högfrekventa automatiska mätningar.

Variabler:
Date, Year, Month, Week, Depth Stratification, Layer, Sec., pH, Alk, Cond, Col, Tur, SPM, SPOM, COD, Chl a, MRP/PO4-P, PP, dissP, SUP, Tot-P, NH4, NO2, NO3, NO2+NO3, PN dissN, Tot-N, Si

Det är fritt fram att använda data från vårt monitoringprogram, men vi vill att ni som använder data ska informera oss så att vi kan hålla reda på vilka projekt som utnyttjar Erkens monitoringprogram.
Vattenkemidata från sjön Erken, 1989-2015
Keywords: AQUATIC ECOSYSTEMS; LAKE/POND; Environmental Sciences; Miljövetenskap; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser